Form and Meaning of Tanah Lot Tourism Brochure from Indonesian to English : A Translation Study - Djami, Kessy Anggreni; Erfiani, Ni Made Diana; Awololon, Yohanes Octovianus Lesu (Kajian Linguistik dan Sastra, 2026)
This study aims to analyze the forms and meanings found in the translation of the Tanah Lot tourism brochure from Indonesian into English by applying Larson’s (1988) theory of form-based and meaning-based translation and Leech’s (1981) theory of the seven types of meaning. This study employed a descriptive qualitative method, using the bilingual Tanah Lot tourism brochure as the primary data source. The data were collected through document analysis and classified according to translation forms and meaning types. The findings reveal two translation forms in the brochure: form-based translation and meaning-based translation. Four data were identified as form-based translation, while seven data were categorized as meaning-based translation. Form-based translation was mainly used for proper names, locational descriptions, operational information, and institutional labels, whereas meaning-based translation was applied to culturally and spiritually significant expressions. The analysis also shows that conceptual meaning is the most dominant type of meaning, followed by connotative, social, affective, reflected, and collocative meanings. The study concludes that meaning-based translation is more effective in conveying cultural concepts and maintaining naturalness, while form-based translation is suitable for preserving factual information in tourism texts. Abstrak Penelitian ini bertujuan untuk menganalisis bentuk dan makna yang terdapat dalam terjemahan brosur wisata Tanah Lot dari bahasa Indonesia ke bahasa Inggris dengan menggunakan teori penerjemahan berbasis bentuk dan berbasis makna dari Larson (1988) serta teori tujuh jenis makna dari Leech (1981). Penelitian ini menggunakan metode deskriptif kualitatif dengan brosur wisata bilingual Tanah Lot sebagai sumber data utama. Data dikumpulkan melalui analisis dokumen dan diklasifikasikan berdasarkan bentuk penerjemahan serta jenis makna. Hasil penelitian menunjukkan adanya dua bentuk penerjemahan dalam brosur, yaitu penerjemahan berbasis bentuk dan penerjemahan berbasis makna. Sebanyak empat data termasuk dalam penerjemahan berbasis bentuk dan tujuh data termasuk dalam penerjemahan berbasis makna. Penerjemahan berbasis bentuk digunakan pada nama diri, deskripsi lokasi, informasi operasional, dan label institusional, sedangkan penerjemahan berbasis makna digunakan pada ungkapan yang mengandung unsur budaya dan spiritual. Analisis juga menunjukkan bahwa makna konseptual merupakan jenis makna yang paling dominan, diikuti oleh makna konotatif, sosial, afektif, reflektif, dan kolokatif. Penelitian ini menyimpulkan bahwa penerjemahan berbasis makna lebih efektif dalam menyampaikan konsep budaya dan menjaga kealamiahan bahasa sasaran, sedangkan penerjemahan berbasis bentuk lebih sesuai untuk mempertahankan informasi faktual dalam teks pariwisata.